2019
DOI: 10.1177/2150135119884916
|View full text |Cite
|
Sign up to set email alerts
|

Atrioventricular Valve Repair in Single Ventricle Physiology: Timing Matters

Abstract: Objectives: Atrioventricular valve (AVV) regurgitation in patients with single ventricle (SV) physiology severely impacts prognosis; the appropriate timing for surgical treatment is unknown. We sought to study the results of surgical treatment of AVV regurgitation in SV patients and evaluate risk factors for mortality. Methods: Medical records of 81 consecutive patients with moderate or severe AAV regurgitation who were submitted to AVV repair or replacement during any stage of univentricular palliation betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…It has been demonstrated that there is an association between AVV repair effectiveness and the timing of intervention. 3,19-23 For adults with native aortic valve pathology, declining EF and LV dilation are key data points in this regard. 22 In our small cohort, the EF after SSLV intervention remained relatively stable.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that there is an association between AVV repair effectiveness and the timing of intervention. 3,19-23 For adults with native aortic valve pathology, declining EF and LV dilation are key data points in this regard. 22 In our small cohort, the EF after SSLV intervention remained relatively stable.…”
Section: Discussionmentioning
confidence: 99%
“…Our objective was to translate TPS into the Portuguese language and to validate its utility and significance in a developing country with less predictable outcomes for CHD surgery [ 14 - 17 ] .…”
Section: Introductionmentioning
confidence: 99%